Effects of Different Land Uses on Availability of Three Major Soil Nutrients in Wet Zone Low Country 3 (WL3) Agro-Ecological Region, Sri Lanka - Seneviratne, H.T.J; Norbert, S.A. (University of Colombo, 2015)
High population density and population distribution percentage coupled with uncontrolled industrialization and urbanization due to the expansion of development activities, increase the pressure exerted on land resource, especially in peri-urban areas such as Gampaha District in Sri Lanka. Hence, land area under the administrative boundary of Gampaha District belongs to Wet zone Low country 3 (WL3) agro ecological regions, also shows a higher affinity to population pressure exerted on land resource. Furthermore, soil quality decline due to the extensive pressure on land is one of the three major soil degradation processes of Sri Lanka. Also, an anthropogenic induced variation in soil nutrient dynamics plays a key role in soil quality decline in the country (Mapa, 2003). Thus, if the depleted nutrients are not properly replenished or surplus inputs were not remediated properly, decline of soil quality will be accelerated. It is therefore necessary to determine the extent to which land use affects nutrient availability of soil to maintain and improve soil quality of different land uses such as agriculture
Keywords: Effects of Different Land Uses on Availability of Three Major Soil Nutrients in Wet Zone Low Country 3 (WL3) Agro-Ecological Region, Sri Lanka